Cults: to be or not to be: exploring the topic of cults within anthropology - Fischer, Jamie (My University, 2020)
Despite the significance of cults as a social group in other disciplines, anthropologists have paid little attention to these sub-cultures as a viable area of research. Social scientists in other disciplines, such as sociology and psychology, have explored cults as a social and mental phenomenon; yet, anthropological investigations tend to be limited to studying cargo cults outside North America. Sociologists have defined and categorized cults in numerous ways: as a social movement or a religious movement. In this presentation, I hypothesize that anthropologists do not study cults due to their methodological practices and theoretical approach to working with communities.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)
Keywords: cults; research methods; anthropology